Pengaruh Harga dan Pengalaman Pelanggan terhadap Tingkat Penjualan dengan Citra Merek sebagai Variabel Intervening pada Kopi Kenanggan Ruko Sutomo di Kota Padang - Dalila Putra; Yulasmi Yulasmi; Yeki Candra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to test how much influence Price and Customer Experience have on Sales Level with Brand Image as an Intervening Variable at Kopi Kenangan Ruko Sutomo in Padang City. The sample in this study amounted to 100 respondents on customers at Kopi Kenangan. This population is customers of Kopi Kenangan Ruko Sutomo in Padang City. The results of this study are (1) There is a positive and significant influence between Price and Brand Image at Kopi Kenangan Ruko Sutomo in Padang City. (2) There is a positive and significant influence between Customer Experience and Brand Image at Kopi Kenangan Ruko Sutomo in Padang City. (3) There is a positive and significant influence between Price and Sales Level at Kopi Kenangan Ruko Sutomo in Padang City. (4) There is a negative and insignificant influence between Customer Experience and Sales Level at Kopi Kenangan Ruko Sutomo in Padang City. (5) There is a positive and significant influence between Brand Image and Sales Level at Kopi Kenangan Ruko Sutomo in Padang City. (6) Brand Image is able to mediate Price and Sales Level at Kopi Kenangan Ruko Sutomo in Padang City. (7) Brand Image is able to mediate Customer Experience and Sales Level at Kopi Kenangan Ruko Sutomo in Padang City.